Effect of economic growth on employment in Sub-Saharan Africa. - Ndung’u, Francis Kamau; Xiongying, Professor Niu (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2021)
The study aimed at investigating the effect of economic growth on employment in Sub-Saharan African. The study employed secondary data that was sourced from the World Bank, World development indicators and FAOSTAT covering 30 Sub Saharan African Countries for the period 1990 to 2015. The study employed the traditional neo-classical aggregate production function in its estimation of the regression results. The panel data obtained was analysed using the STATA software program. Hausman test was used and it determined that fixed effects estimation was preferred to random effects estimation and therefore fixed effects regression was used during the analysis. Empirical results on effect of economic growth on employment established that total employment, women in employment and men in employment statistically and significantly influenced economic growth and on the other hand economic sectors which comprised of domestic capital, imports, exports and services sectors statistically and significantly influenced economic growth.